Gender in Philippine advertisements portrayal patterns and platform differences immediately before the COVID-19 pandemic - Paragas, Fernando; Rapanot, Czekaina Esrah; Mangalus, Marrhon; Hoggang, Catherine Faith; Agonos, Mariam Jayne (2022)
Access online through this link: https://www.plarideljournal.org/article/gender-in-philippine-advertisements-portrayal-patterns-and-platform-differences-immediately-before-the-covid-19-pandemic
Keywords: Advertising; COVID-19 pandemic; Gender role in advertising